PERLINDUNGAN HUKUM TERHADAP PENDAFTARAN MEREK DYLEE & LYLEE YANG SUDAH DIALIHKAN (STUDI PUTUSAN KOMISI BANDING MEREK NO 429/KBM/HKI/2021): Legal Protection For Dylee & Lylee Brand Registrations That Have Been Transferred (Study Of The Mark Appeal Commision’s Decision No 429/KBM/HKI/2021) - Aryo Dewantoro; Dian Purnamasari (AMICUS CURIAE, 2025)
Guangdong Kuaike Ltd registered its trademark named Dylee & Lylee in class 14. The identification of the problem in this research is the registration obstacle faced by Guangdong Kuaike Ltd due to the existence of the Dylee & Lylee trademark in class 3 owned by Yumin Qin. Subsequently, an agreement for the transfer of rights to the Dylee & Lylee trademark in class 3, previously owned by Yumin Qin, was made to Guangdong Kuaike Ltd. After the rights transfer, Guangdong Kuaike Ltd filed an appeal against the registration of its trademark in class 14, but the Trademark Appeal Commission still rejected it. Data analysis was conducted descriptively with deductive conclusion drawing. Based on the research results and conclusions, it is concluded that the legal protection received by Guangdong Kuaike Ltd as the owner and holder of the Dylee & Lylee trademark is not fully secured because the transferred trademark cannot be re-registered.